2015
DOI: 10.1515/ijamh-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sickle cell disease readiness for transition assessment

Abstract: Our results support that the TIP-RFT is a valid and reliable tool for the assessment of transition readiness for youths with SCD. The TIP-RFT assessment can guide interventions to improve transition readiness and can provide a foundation for future research on other variables that might be associated with transition readiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…At the KATH SCC, adolescents and their accompanying adult family members were asked about a range of topics that have previously been identified as important for successful transition to adult SCD care in the U.S and U.K [ 13 , 23 ] . To our knowledge, this is the first patient survey about SCD transition in Ghana or elsewhere in Africa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the KATH SCC, adolescents and their accompanying adult family members were asked about a range of topics that have previously been identified as important for successful transition to adult SCD care in the U.S and U.K [ 13 , 23 ] . To our knowledge, this is the first patient survey about SCD transition in Ghana or elsewhere in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Interview questions had been adapted from two surveys that previously had been used to assess transition readiness and transition related concerns of adolescents in the U.S.: Sickle Cell Transfer Questionnaire (SCTQ) [ 13 ] and Transition Intervention Program Readiness for Transition (TIP-RFT) [ 23 ] . Those studies had identified four major domains that were relevant to SCD transition from pediatric to adult care cited above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four of the 19 tools used in the included articles were developed prior to 2014 [11,32,37,43]. Of the 15 [11,26,32,37,43,47,49,51,53,[55][56][57], and among the 48 included, articles have been utilized in Argentina [21], Brazil [19], Canada [3,15,16,23], Mexico [33], and Turkey [22]. Three tools originated in Canada [39,41,45] and have been utilized in Japan [46] and Turkey [42].…”
Section: Characteristics Of Measuresmentioning
confidence: 99%
“…Camp can be excellent preparation for the transition to the adult medical care system, widely recognized as an important goal for SCD education. [22][23][24] Informal teaching methods such as role-playing skits, games, 25,26 music, 27,28 or movies (eg, The Family Legacy produced by UK Sickle Cell Society 29 and Spilled Milk -A Documentary by Jaqai Mickelsen and Omar Beach 30 ) fit well into the spirit of summer camp.…”
Section: Education In Self-carementioning
confidence: 99%